2020
DOI: 10.1177/1060028020908067
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Steroid Treatment for Sudden Sensorineural Hearing Loss: A Meta-analysis of Randomized Controlled Trials

Abstract: Background: The best way to administer steroids for sudden sensorineural hearing loss (SSHL) is still unclear. The present study was aimed at estimating the efficacy of steroids by intratympanic, systemic, and combined therapy (CT) routes. Methods: A systematic literature search was performed from 1950 to October 2019 for randomized controlled trials comparing the use of intratympanic, systemic, and combined steroid therapy for SSHL. The outcomes of recovery rate and pure tone average (PTA) improvement were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
1
16
0
2
Order By: Relevance
“…[15][16][17] Many studies showed favor-able results with the use of combined treatment with systemic and IT steroids. 18,19) Superiority of Group 3 over Group 1 is a prominent result in the present study. Some factors may be associated with this result as follows: differences in admission period, duration of steroid activity, and steroid dose.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…[15][16][17] Many studies showed favor-able results with the use of combined treatment with systemic and IT steroids. 18,19) Superiority of Group 3 over Group 1 is a prominent result in the present study. Some factors may be associated with this result as follows: differences in admission period, duration of steroid activity, and steroid dose.…”
Section: Discussionsupporting
confidence: 59%
“…Dexamethasone has a longer duration of action compared with prednisolone. 19) Duration of action of prednisolone and dexamethasone was 12-36 and 36-72 h, respectively. Although the total duration of steroid was similar, long-acting steroids may be associated with greater cumulative dose and longer effect of steroid that those associated with short-acting steroids.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic steroids (SS) and transtympanic steroids (TTS) are the two main delivery methods of corticosteroid therapy utilized in SSNHL treatment. Although no widespread consensus exists regarding the superiority of one method over the other for improving hearing outcomes, TTS have gained popularity among treating physicians over the years as a growing body of evidence has supported their use as either salvage therapy or initial therapy in conjunction with SS ( 4 – 7 ). Moreover, TTS offer several advantages over SS, including a reduced systemic side effect profile, potentially increased drug delivery to the inner ear, and better suitability for patients in which SS may be contraindicated (e.g., diabetes mellitus, peptic ulcer disease, immunocompromised) ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inner ear diseases have been treated by systemic drug delivery systems via the oral route, intramuscular, or intravenous (Ruckenstein, 2004;Alexander et al, 2009;Buniel et al, 2009;McCall et al, 2010;Li et al, 2017). For example, corticosteroids are widely used to treat sudden SHL and have been found to be efficient with a recovery rate of 61%, which is much higher than using a placebo (recovery rate of 32%) demonstrated by Li and Ding (2020). Recently, it was reported that the recovery rates of SHL could reach up to 57-66% with oral corticosteroid (Filipo et al, 2014;Chen et al, 2015).…”
Section: Systemic Drug Deliverymentioning
confidence: 99%